2022
DOI: 10.3389/fcell.2022.845293
|View full text |Cite
|
Sign up to set email alerts
|

Identification of A Risk Signature Based on Lactic Acid Metabolism-Related LncRNAs in Patients With Esophageal Squamous Cell Carcinoma

Abstract: Lactic acid, formerly thought of as a byproduct of glycolysis or a metabolic waste produced, has now been identified as a key regulator of cancer growth, maintenance, and progression. However, the results of investigations on lactic acid metabolism-related long non-coding RNAs (LRLs) in esophageal squamous cell carcinoma (ESCC) remain inconclusive. In this study, univariate Cox regression analysis was carried out in the TCGA cohort, and 9 lncRNAs were shown to be significantly associated with prognosis. Least … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…2022-R241) and informed written consent was obtained from all patients. The specific experimental protocol comes from our previous research ( 10 , 11 ).…”
Section: Methodsmentioning
confidence: 99%
“…2022-R241) and informed written consent was obtained from all patients. The specific experimental protocol comes from our previous research ( 10 , 11 ).…”
Section: Methodsmentioning
confidence: 99%
“…The study has obtained the approval of The Ethics Committee of the Second Hospital of Hebei Medical University and obtained all patients' written consent. For specific experimental protocols, please refer to previous studies in our hospital (15,16).…”
Section: Qrt-pcrmentioning
confidence: 99%
“…Mounting evidence suggested that lncRNAs play an important role in prognosis prediction in ESCC. For example, prognostic signatures such as lactic acid metabolism, ferroptosis-related lncRNA, and m7G-related lncRNA were proved to have favorable prognosis prediction in ESCC [12][13][14]. In addition, lncRNA based model can be used as therapeutic target, which could forecast the effect of immunotherapy or chemotherapy [15,16].…”
Section: Introductionmentioning
confidence: 99%